Peter Tyndall - Tyndall, Peter, 1951-; Hiscock, Rose; Comte, Samantha; Roberts, Claire; Hall, Doug; Aitken, Annika; Maidment, Simon; Buxton Contemporary Art Museum ([Southbank, Victoria] : Buxton Contemporary, 2023)
This is the first major retrospective exhibition of one of Australia’s most influential artists, Peter Tyndall. Maintaining a rigorous studio practice spanning 50 years, Tyndall‘s expansive works contemplate the fundamental questions about the construction of meaning. Tyndall interrogates how art, language, presence and absence operate in relation to one another in comprehending the world around us. Reflecting on his unwavering commitment to this way of seeing the world, Tyndall created a unique set of symbols to describe his philosophical framework where he structured his entire artistic practice. The exhibition demonstrates Tyndall’s process from making art, innovation, and life-long dedication to insatiable productivity. Celebrating Tyndall’s remarkable career, this exhibition charts the development of his philosophical framework for seeing and viewing art – and ourselves – in relation to the world around us. In November 1974, Tyndall began to use a unique set of symbols to describe this relationship, including his iconic ideogram and repeating title. He continues to use these devices today, structuring his entire artistic practice around this insight. Featuring over 200 works encompassing the entire museum, the exhibition includes paintings, drawings, correspondence art, and unseen works ranging back to the 1970s. The exhibition will draw from the University’s significant collection alongside artworks on loan from national institutions and private collections. For Tyndall, making art is a collective endeavour and the interconnectedness of all things is at the core of his practice. Peter Tyndall reminds us that we are not alone, and the viewer is an active participant in the art-making process. -- Buxton Contemporary website (accessed July 10th, 2023)
Edited by Annika Aitken ; foreword by Rose Hiscock ; introduction by Samantha Comte ; texts by Peter Tyndall , Claire Roberts, Doug Hall.
Curated by Samantha Comte, Senior Curator Art Museums, University of Melbourne, and Dr Simon Maidment.
Exhibition held 9 December 2022 - 16 April 2023 Buxton Contemporary
Keywords: Tyndall, Peter, -- 1951- -- Exhibitions; Painting -- Australia -- 20th century; Painting -- Australia -- 21st century; Art, Modern -- Australia -- Exhibitions; Writing in art -- Exhibitions; Australian